Ideal MHD - Freidberg, Jeffrey P. (Cambridge: Cambridge University Press, 2014)
"Comprehensive, self-contained, and clearly written, this successor to Ideal Magnetohydrodynamics (1987) describes the macroscopic equilibrium and stability of high temperature plasmas - the basic fuel for the development of fusion power. Now fully updated, this book discusses the underlying physical assumptions for three basic MHD models: ideal, kinetic, and double-adiabatic MHD. Included are detailed analyses of MHD equilibrium and stability, with a particular focus on three key configurations at the cutting-edge of fusion research: the tokamak, stellarator, and reversed field pinch. Other new topics include continuum damping, MHD stability comparison theorems, neoclassical transport in stellarators, and how quasi-omnigeneity, quasi-symmetry, and quasi-isodynamic constraints impact the design of optimized stellarators. Including full derivations of almost every important result, in-depth physical explanations throughout, and a large number of problem sets to help master the material, this is an exceptional resource for graduate students and researchers in plasma and fusion physics"--
Machine generated contents note: 1. Introduction; 2. The ideal MHD model; 3. General properties of ideal MHD; 5. Equilibrium: one-dimensional configurations; 6. Equilibrium: two-dimensional configurations; 7. Equilibrium: three-dimensional configurations; 8. Stability: general considerations; 9. Alternate MHD models; 10. MHD stability comparison theorems; 11. Stability: one-dimensional configurations; 12. Stability: multi-dimensional configurations; Appendix A. Heuristic derivation of the kinetic equation; Appendix B. The Braginskii transport coefficients; Appendix C. Time derivatives in moving plasmas; Appendix D. The curvature vector; Appendix E. Overlap limit of the high b and Greene-Johnson stellarator models; Appendix F. General form for q(y); Appendix G. Natural boundary conditions; Appendix H. Upper and lower bounds on dQKIN.
Updated version of: Ideal magnetohydrodynamics. 1987.
Keywords: Magnetohydrodynamics -- Mathematical models; Fluid dynamics -- Mathematical models; Turbulence -- Mathematical models; High temperature plasmas; Plasma (Ionized gases); Fusion reactors; SCIENCE / Physics